2022
DOI: 10.3390/ijerph192315977
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Role Ambiguity and Workers’ Creativity during the COVID-19 Pandemic in China

Abstract: Job role ambiguity is becoming more and more common due to the increase in telecommuting caused by the COVID-19 epidemic. In order to understand the internal mechanism of the association between role ambiguity and creativity, this study examined it in the context of the Demands–Resources–Individual Effects (DRIVE) model. Participants were employees from all walks of life in mainland China, with a total of 437 valid data. The results showed that role ambiguity had no significant direct effect on creativity but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Some studies failed to find a significant relationship between role ambiguity and innovative behaviors [13], while others found a significant negative correlation [102]. Research on innovation has shown that when distracted by other goals, people automatically engage in habitual behavior rather than innovative behavior [13]. Role ambiguity is negatively correlated with innovation performance, the finding supported by a few studies [103,104].…”
Section: The Mediating Role Of Role Ambiguitymentioning
confidence: 99%
See 4 more Smart Citations
“…Some studies failed to find a significant relationship between role ambiguity and innovative behaviors [13], while others found a significant negative correlation [102]. Research on innovation has shown that when distracted by other goals, people automatically engage in habitual behavior rather than innovative behavior [13]. Role ambiguity is negatively correlated with innovation performance, the finding supported by a few studies [103,104].…”
Section: The Mediating Role Of Role Ambiguitymentioning
confidence: 99%
“…The DRIVE model is a comprehensive and flexible theory. It integrates the combined effects of various work demands, work resources, and personal resources on individual health, behavioral outcomes, organizational outcomes, and other outcome variables [13,27,28]. Flexible work arrangements are seen as job demands, making employees isolated from their leaders and colleagues in time and space, prone to information lag as well as incomplete information transfer, and causing depletion of individual resources [29].…”
Section: The Demands-resources-individual Effects (Drive) Modelmentioning
confidence: 99%
See 3 more Smart Citations